(untitled) (Research, Society and Development, 2022)
Miersiella umbellata (Miers) Urb. is a mycoheterotrophic species of the Burmanniaceae family easily recognized by its umbelliform inflorescence and the 2-lobed glands on the top of the ovary. According to the scientific literature, this species has a confirmed occurrence in the Brazilian Atlantic Forest and in Amazonian parts of other countries. In this work we report the first record of M. umbellata in the Brazilian Amazon, expanding its distribution in Brazil. We also present description, comments, illustrations, and a map showing the collection points of M. umbellata in the region. So far, all known records of M. umbellata in the Brazilian Amazon have been made in “terra firme” forests located in Conservation Units (Serra do Acará State Park, in the state of Amazonas; Terra Grande Pracuúba Extractive Reserve, and Utinga State Park, both in the state of Pará).